Zur Wirkung externaler versus internaler Aufmerksamkeitsfoki beim Erlernen einer Bewegungsfertigkeit mit proximalem Effekt - Bund, A.; Gass, S.; Weidenauer, J. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
Recent findings indicate that giving instructions and feedback that direct the lea-rner`s attention not to the movement execution (internal focus) but to the effect of the movement (external focus) are more effective for motor learning. Most of the studies, however, used movements which produced distant effects. The pur-pose in the present study was to examine wether the attentional focus also plays a role in learning motor skills with a proximal effect. Participants (N = 16) practiced riding on a pedalo and received instructions that induced either an internal or an external focus. No significant differences between the groups were found. The results suggest that the effect of attentional focus depends on the task.